Religious Tolerance Narratives on Social Media: Network Analysis of Indonesian Civil Society Organizations on Instagram (2019–2023) - Rohmawati, Wiwin Siti Aminah; Hamidah, Kamilia (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
This study examines the role of Indonesian Civil Society Organizations (CSOs) in promoting religious tolerance narratives through social media, particularly Instagram, from 2019 to 2023. The research addresses the challenges CSOs face in countering intolerance and polarization online, emphasizing the digital strategies they employ. Utilizing a Discourse Network Analysis (DNA) method, the study integrates quantitative network mapping and qualitative text analysis to explore content patterns, collaborations, and audience engagement. Primary data was collected from 25 CSO Instagram accounts, supported by textual analysis, observations, interviews, and documentation. The research focuses on two key questions: (1) What do CSO networks promoting interfaith tolerance look like? and (2) How are narratives of tolerance structured and disseminated within these networks? Findings highlight variations in CSO strategies, showing that highly active organizations achieve broader reach through consistent posting, while smaller CSOs rely on quality content and partnerships to remain impactful. Despite algorithmic challenges and echo chambers, CSOs effectively leverage social media to advance tolerance narratives, integrating cultural and religious contexts. The study underscores the need for collaborative networks and adaptive digital strategies to amplify inclusive messages and mitigate intolerance, offering insights into strengthening CSO efforts in the digital era.